Financial education and financial satisfaction: Financial literacy, behavior, and capability as mediators. Issue 5 (3rd July 2017) - Xiao, Jing Jian; Porto, Nilton
Abstract : Purpose: The purpose of this paper is to investigate roles of financial literacy, financial behavior, and financial capability as mediating factors between financial education and financial satisfaction. Design/methodology/approach: Data are from the 2012 National Financial Capability Study, a large national data set with detailed information on financial satisfaction, education, literacy, behavior, capability, and related variables. Mediation analyses are used to answer research questions. Findings: Financial education may affect financial satisfaction, a subjective measure of financial well-being, through financial literacy, financial behavior, and financial capability variables. Results show that subjective financial literacy, desirable financial behavior and a financial capability index (a sum of Z-scores of objective financial literacy, subjective financial literacy, desirable financial behavior, and perceived financial capability) are strong mediators between financial education and financial satisfaction. Research limitations/implications: The study has used cross sectional data that can only document associations between financial education and satisfaction and the mediators between them. Future research could use relevant longitudinal data to verify multiple benefits of financial education. Practical implications: The findings have implications for financial service professionals to take advantages of multiple benefits of financial education in content acquisition, confidence in knowledge and ability, and action taking when they communicate with their clients. Social implications: Policy makers on consumer financial education may use the information to advocate and promote effective education programs to improve consumer financial well-being. Originality/value: This study is the first of this kind to examine the association between financial education and financial satisfaction and several financial capability variables as mediating factors.